Human-umbilical cord matrix mesenchymal cells improved left ventricular contractility independently of infarct size in swine myocardial infarction with reperfusion - Raposo, Luís; Cerqueira, Rui J.; Leite, Sara; Moreira-Costa, Liliana; Laundos, Tiago L.; Miranda, Joana O.; Mendes-Ferreira, Pedro; Coelho, João Almeida; Gomes, Rita N.; Pinto-do-Ó, Perpétua; Nascimento, Diana S.; Lourenço, André P.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Human umbilical cord matrix-mesenchymal stromal cells (hUCM-MSC) have demonstrated beneficial effects in experimental acute myocardial infarction (AMI). Reperfusion injury hampers myocardial recovery in a clinical setting and its management is an unmet need. We investigated the efficacy of intracoronary (IC) delivery of xenogeneic hUCM-MSC as reperfusion-adjuvant therapy in a translational model of AMI in swine. Methods In a placebo-controlled trial, pot-belied pigs were randomly assigned to a sham-control group (vehicle-injection; n = 8), AMI + vehicle (n = 12) or AMI + IC-injection (n = 11) of 5 × 105 hUCM-MSC/Kg, within 30 min of reperfusion. AMI was created percutaneously by balloon occlusion of the mid-LAD. Left-ventricular function was blindly evaluated at 8-weeks by invasive pressure-volume loop analysis (primary endpoint). Mechanistic readouts included histology, strength-length relationship in skinned cardiomyocytes and gene expression analysis by RNA-sequencing. Results As compared to vehicle, hUCM-MSC enhanced systolic function as shown by higher ejection fraction (65 ± 6% vs. 43 ± 4%; p = 0.0048), cardiac index (4.1 ± 0.4 vs. 3.1 ± 0.2 L/min/m2; p = 0.0378), preload recruitable stroke work (75 ± 13 vs. 36 ± 4 mmHg; p = 0.0256) and end-systolic elastance (2.8 ± 0.7 vs. 2.1 ± 0.4 mmHg*m2/ml; p = 0.0663). Infarct size was non-significantly lower in cell-treated animals (13.7 ± 2.2% vs. 15.9 ± 2.7%; Δ = −2.2%; p = 0.23), as was interstitial fibrosis and cardiomyocyte hypertrophy in the remote myocardium. Sarcomere active tension improved, and genes related to extracellular matrix remodelling (including MMP9, TIMP1 and PAI1), collagen fibril organization and glycosaminoglycan biosynthesis were downregulated in animals treated with hUCM-MSC. Conclusion Intracoronary transfer of xenogeneic hUCM-MSC shortly after reperfusion improved left-ventricular systolic function, which could not be explained by the observed extent of infarct size reduction alone. Combined contributions of favourable modification of myocardial interstitial fibrosis, matrix remodelling and enhanced cardiomyocyte contractility in the remote myocardium may provide mechanistic insight for the biological effect.